Safety and efficacy of ultrasound-guided thermal ablation in treating T1aN0M0 and T1bN0M0 papillary thyroid carcinoma: A meta-analysis - Wang, Mei-Huan; Liu, Xiao; Wang, Qian; Zhang, Hua-Wei (Frontiers in Endocrinology, 2022)
Background Papillary thyroid cancer (PTC) is the most common thyroid tumor, and early diagnosis and treatment can effectively improve prognosis. It has many controversies regarding the treatment method of T1N0M0 PTC. Recently, thermal ablation (TA) has shown some benefits in the treatment of PTC patients, but the safety and efficacy of its treatment remain controversial. This article performs a meta-analysis of TA in patients with T1aN0M0 and T1bN0M0 PTC. Methods The PubMed, Embase, Web of Science, and Cochrane Library databases were systematically searched for retrospective or prospective studies of thermal ablation for treating patients with T1aN0M0 and T1bN0M0 PTC from the database establishment to May 1, 2022. Data on volume reduction rate (VRR), disease progress, and complication rate were collected. In addition, a meta-analysis was performed using the Stata 12.0 and Review Manager 5.3. Results A total of 9 eligible studies were included. Our study demonstrated the effectiveness of VRR and disease progress. The VRR was reduced after 3 months (-75.90%; 95%CI [-118.46~33.34%]), 6months (34.33%; 95%CI [15.01~53.65%]), 12months (78.69%; 95%CI [71.69~85.68%]) and 24 months (89.97%; 95%CI [84.00~95.94%]). The disease progress was 1.9%, (95%CI [1.1-3.0]). Safety is justified by complication rates, which were 6.5%, (95%CI [3.5-10.2]). Pain and hoarseness were the most common complications and no life-threatening complications were reported. The Egger’s test demonstrated publication bias was acceptable. Conclusions TA is an effective and safe method for managing T1aN0M0 and T1bN0M0 papillary thyroid nodules.